The Characteristics of Solid Soap with Varied Additions of Kefir Cheese Whey - Solikah, Solikah; Kurniawan, Kurniawan; Husna, Ashiqotul; Nuha Pitaloka, Isyana (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Kefir cheese whey is a product of fermented cheese whey wastewaste. Kefir cheese whey has been known to contain Lacofferin. Lactoferrin functions as an antimicrobial. Methods: This study focuses on producing solid soap from kefir cheese whey. The saponification reaction of saponification reaction of coconut and palm oil, with Natrium Hidroxide with kefir cheese whey, initiated the solid soap production. Results: show that all formulae of solid soap from kefir cheese whey showed good physicochemical characteristics, pH 10.09–10.98 (ASTM requirement 9-11), foam content 10.98-12.89. Soap Kefir cheese whey can be concluded that all formulas meet the requirements that all formulas meet the requirements established by SNI 3532:2016 and ASTM D 2022. Conclusions: The Best formula for solid soap variant kefir is 100 % whey. Thus, the giving of kefir whey is recommended for manufacturing kefir soap. It suggests that soap kefir cheese whey is recommended for use as an antibacterial agent in the manufacture of solid soap.